2022
DOI: 10.2147/opth.s351932
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes from the Retrospective Multicenter Cross-Sectional Study on Lamellar Macular Hole Surgery

Abstract: Purpose To analyze the functional and anatomical parameters of lamellar macular hole (LMH) surgery with internal limiting membrane peeling and determine which surgical technique provides the best visual outcome. Methods This is a retrospective multicenter cross-sectional study on patients who underwent pars plana vitrectomy (PPV) for LMH with or without combined phaco-vitrectomy, as well as gas-, air- or BSS-tamponade. Pre- and postoperative examination included best co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Invariably many of the early series included both ERM foveoschisis and LMH eyes without differentiating between these two different conditions. Some authors suggest that there is no evidence that justifies PPV [ 8 , 10 , 11 ], while others feel that vitrectomy should be reserved for cases where the visual acuity continues to decrease or when the macula experiences progressive macular thinning [ 27 , 112 ]. Others have shown that PPV with ERM and ILM removal improves the visual and anatomic outcomes [ 10 , 12 , 13 , 113 , 114 , 115 , 116 , 117 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Invariably many of the early series included both ERM foveoschisis and LMH eyes without differentiating between these two different conditions. Some authors suggest that there is no evidence that justifies PPV [ 8 , 10 , 11 ], while others feel that vitrectomy should be reserved for cases where the visual acuity continues to decrease or when the macula experiences progressive macular thinning [ 27 , 112 ]. Others have shown that PPV with ERM and ILM removal improves the visual and anatomic outcomes [ 10 , 12 , 13 , 113 , 114 , 115 , 116 , 117 ].…”
Section: Treatmentmentioning
confidence: 99%
“…A moderate consensus was reached in the remaining items. Among them, it emerged that surgeons still feel safer tamponading LMH with SF 6 instead of BSS (Haave et al, 2022). Noteworthy, all the items pertaining the approach of refractory or recurrent FTMH showed only a moderate consensus among all the participants.…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of retinal conditions exist that require pars plana vitrectomy (PPV) and subsequent injection of a vitreous substitute into the vitreous chamber such as retinal detachment (RD), proliferative diabetic retinopathy, macular holes and ocular trauma [ 1 , 2 , 3 , 4 , 5 ]. Among these, RDs treated with PPV are the cornerstone condition in which all the properties of an artificial, temporary vitreous substitute come into play for a successful clinical and anatomical result [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%